Wireless and Flexible Optoelectronic System for In Situ Monitoring of Vaginal pH Using a Bioresorbable Fluorescence Sensor. Issue 8 (5th February 2023) - Paghi, Alessandro; Corsi, Martina; La Mattina, Antonino A.; Egri, Gabriella; Dähne, Lars; Barillaro, Giuseppe
Abstract: Herein, a miniaturized wireless sensing vaginal ring for the in situ continuous monitoring of vaginal pH and real‐time transmission of the pH data to a smartphone is reported, aimed at the diagnosis and management of bacterial vaginosis, a common condition frequently and adversely affecting women. The sensing vaginal ring consists of a bioresorbable pH fluorescence sensor placed on top of a polydimethylsiloxane ring encapsulating a miniaturized driving/readout optoelectronic circuit, data acquisition system, wireless transceiver, and power supply. The pH sensor consists of a micrometer‐thick porous silica scaffold conformably coated with a nanometer‐thick polymer multilayer stack and is intended to be replaced after 4 days. The sensor fully dissolves in biocompatible by‐products eliminating waste management issues; conversely, the ring embedding the circuit is reusable with new sensors. The pH sensor, as well as the sensing vaginal ring, show excellent performance in the continuous measurement of pH in vaginal fluid and can monitor the pH level over the physio‐pathological range of 3–7.5 with high linearity, accuracy, and reliability, transmitting the data to a smartphone in real time. The proposed technology can be immediately translated to other diseases, among which wound healing, intragastric activity, and cancer progression, where continuous monitoring of pH is required, as well as to other markers/analytes by engineering the polymer stack with suitable receptors, such as aptamers and other molecular probes. Abstract : A wireless, sensing vaginal ring for in situ continuous monitoring of pH and real‐time transmission of data to a smartphone is reported, featuring a bioresorbable pH sensor placed on a silicone ring encapsulating a driving/readout circuit, data acquisition system, wireless transceiver, and power supply. The sensor dissolves in biocompatible by‐products eliminating waste management issues; the ring embedding the circuit is reusable.